Synthesis and Antimicorbial Studies of Some Azetidinone Derivatives from 8-Hydroxy Quinoline - ISHWAR BHAT, K.; MAITY, SUPRIYA; SUBRAHMANYAM, E.V.S. (Asian Journal of Chemistry, 2010)
A new series of azetidinone derivatives have been synthesized. Structures of these azetidinone derivatives have been confirmed by analytical and spectral data. The compounds have also been screened for antibacterial and antifungal activity.